1997
DOI: 10.1093/oxfordjournals.aje.a009163
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Controls versus Community Controls: Differences in Inferences Regarding Risk Factors for Hip Fracture

Abstract: In case-control studies using cases identified from persons admitted to hospitals, two types of controls are most often used: persons from the communities served by the hospitals and persons admitted to the same hospitals as those to which the cases were admitted. It is often unclear which is the more appropriate choice, and whether the use of one or the other type of control group will lead to biased conclusions. The purpose of the present analysis was to determine whether the choice of hospital controls vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…Much has been said about the choice of controls from the community or hospital,29 including for the study of hip fracture 30. Because the controls were admitted to hospital they were obviously ill and therefore had a higher probability of using drugs, perhaps including benzodiazepines, than a healthy control population.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been said about the choice of controls from the community or hospital,29 including for the study of hip fracture 30. Because the controls were admitted to hospital they were obviously ill and therefore had a higher probability of using drugs, perhaps including benzodiazepines, than a healthy control population.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy would have been to select the controls from a hospital population; however, such a group, because of concurrent illness, may not be representative and it may be dif®cult to extrapolate the ®ndings to the general population. Moritz et al [17], in considering this issue, suggested community controls comprise the more appropriate control group in case±control studies of hip fracture in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Cuando se utilizó el concepto de raza con frecuencia la asociación fue modificada por el estrato social [9][10][11][12][13][14][15]23,24 . La raza es un grupo de individuos reunidos por algunas características genéticas comunes, cuyo valor para explicar la variabilidad humana es limitada dado la mayor importancia de la diversidad individual.…”
Section: Discussionunclassified
“…El menor acceso a la atención de salud de los miembros de la etnia mapuche con fractura de fémur proximal se balanceó utilizando controles hospitalarios, donde las dificultades de acceso son las mismas. Sin embargo, como se demostró en la revisión bibliográfica los controles hospitalarios son «más enfermos que los casos» 14 , lo que nos obligó a considerar en el análisis variables de control relacionadas con morbilidad. Otro factor que potencia el sesgo de muestreo es el alto índice de masculinidad de la población mapuche de la IX región (108,2 en Malleco y 103,2 en Cautín) que contrasta con el predominio del sexo femenino en chilenos con fractura de fémur proximal (índice de masculinidad en egresos por fractura de fémur proximal en 1985 66,6).…”
Section: Discussionunclassified
See 1 more Smart Citation